2022
DOI: 10.3390/microorganisms11010063
|View full text |Cite
|
Sign up to set email alerts
|

Lactiplantibacillus plantarum Strains Modulate Intestinal Innate Immune Response and Increase Resistance to Enterotoxigenic Escherichia coli Infection

Abstract: Currently, probiotic bacteria with not transferable antibiotic resistance represent a sustainable strategy for the treatment and prevention of enterotoxigenic Escherichia coli (ETEC) in farm animals. Lactiplantibacillus plantarum is among the most versatile species used in the food industry, either as starter cultures or probiotics. In the present work, the immunobiotic potential of L. plantarum CRL681 and CRL1506 was studied to evaluate their capability to improve the resistance to ETEC infection. In vitro st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…When fed soil bacteria, the innate immune system has been shown to be an important factor for shaping the resulting worm microbiota [24]. The innate immune system is also involved with mediating a beneficial effect of probiotic bacteria [17,43] and it is most likely also determining which subset of the human microbiota can colonize the bacteria. However, many additional genetic factors determining microbiota colonization and effects on the host are likely to exist, which can be studied with a sub-microbiota of cHFM.…”
Section: You Are Not What You Eat-sub-microbiomes Colonize the Worm I...mentioning
confidence: 99%
“…When fed soil bacteria, the innate immune system has been shown to be an important factor for shaping the resulting worm microbiota [24]. The innate immune system is also involved with mediating a beneficial effect of probiotic bacteria [17,43] and it is most likely also determining which subset of the human microbiota can colonize the bacteria. However, many additional genetic factors determining microbiota colonization and effects on the host are likely to exist, which can be studied with a sub-microbiota of cHFM.…”
Section: You Are Not What You Eat-sub-microbiomes Colonize the Worm I...mentioning
confidence: 99%
“…SCFAs are degradation products of undigested carbohydrates by intestinal microorganisms, which could reshape the gut ecology, induce immunomodulatory and antibiotic activity, and mediate infammatory signaling cascade during gut infammation [40]. Banerjee et al found that probiotics seem to improve other characteristics such as SCFAs production [11,12]. Te increased secretion of SCFAs in the intestine acidifes the colonic environment, promotes the absorption of minerals, and combats the invasion of pathogenic bacteria [35,41].…”
Section: Discussionmentioning
confidence: 99%
“…Ren et al reported that the probiotic Lactobacillus paracasei ameliorated diarrhea by inhibiting the activation of the nuclear factor kappa B/MLCK pathway and increasing the abundance of short-chain fatty acids (SCFAs)-producing gut microbiota in mice [11]. In addition, Baillo et al demonstrated that Lactiplantibacillus plantarum strains can modulate intestinal innate immune response, thereby increasing the ETEC clearance in mice [12]. Nevertheless, available evidence also suggests that the antiinvasive efect of probiotics on ETEC is closely related to the type and action mode of probiotics [13,14], which needs further comparative study.…”
Section: Introductionmentioning
confidence: 99%